Impact of the Covid-19 confinement measures on telework in France - A qualitative survey - Francesco S. Massimo (European Commission, Joint Research Centre (JRC), 2020)
During the Covid crisis the population in regime of telework jumped from 3% to 25% of the workforce. This study aims at better understanding how the massive shift to telework following the outbreak of the COVID-19 pandemic affected workers' jobs and lives in France during the first lockdown (March 17th-May 11th 2020). In particular, we shed light on how this exogenous change had an impact on tasks content and work organisation dimensions like teamwork, routine, workers' autonomy and types and extent of supervisory controls method. Moreover, we dig into both subjective and objective dimensions of job quality such as job satisfaction, motivation, changes in working time and pay, together with issues related to physical and mental health and more generally to work-life balance. The picture that emerges is quite fragmented, largely depending on workers' occupation and family composition, although some general patterns could be observed. First, the transition to telework did not affected the structural inequality of the occupational structure: respondents accomplishing low skilled and standardised tasks enjoyed, to a certain extent, more freedom from direct control, whereas interviewees on less standardised and more autonomous tasks were more able to carve out some niches of independence in the new situation and were more able to resist management pressures for more control and standardization. Second, most organisations had no specific policies dedicated to teleworking and workers had to adapt to the new situation without any special guideline: horizontal cooperation emerges as driver of adaptation as important as vertical control, if not more. Third, the positive aspect that was noticed by the large majority of respondents was the opportunity that telework gave them to experiment a more flexible management of time, at least for those who could tinker with their working time schedule. Fourth, and especially for that reason, the overwhelming majority of respondents wishes to consolidate the practice of telework also after the end of the lockdown and with more continuity.
Keywords: 330; Covid-19; Telework; Quality of Work; Management and Workers Power; Labour Process; Employment Relations; Work-Life Balance